Efecto del periodo crítico de competencia de malezas en el rendimiento de arroz (oryza sativa) variedad capirona al trasplante en el Bajo Mayo - Águila Montilla, Daniel Del (2001)
This research was conducted with the objective of determining the effect of the critical period of weed competition on rice yield transplant Capirona variety, the period of competition "global and critical weed with rice" and the analysis economic treatments by cost-benefit balance. The study was conducted between November 1, 2000 until March 15, 2001 on the property of Mrs. Carmen Garcia Ramirez; located in the District of Morales, province of San Martin, under the randomized complete block design with 16 treatments and 3 repetitions. The best yields of paddy were obtained in treatments without weeds throughout the season (T1) (8 352.59 kg / ha) and weeding until 30 to 60 days T1 and T4 (7 826.66 and 7 308.03 kg / ha ), with weeding from 10 and 50 days T14 and T13 (7 y7037.03 394.74 kg / ha) after transplantation. The critical global competition transplant rice with weeds, period ranges from 10 days up to 60 days of transplantation, and the specific period fluctuated or varied from 20 to 30 and 40 to 60 days. Manuals weeded continuous during the arrest and periods of tillering directly affected the performance of rice husk. Predominant weed populations the field were: Cyperus, Jussiaea, Echmochioa, Eichhornia and Ischaenum. The greater height of weeds were recorded: Ischaenum, Jussiaea, Cyperus, Echinochloa and Eichhornia. the 48.41% (484.1 Kg / ha) yield of paddy per 1000 kg of dry weed biomass was lost. The net value of production was only positive in treatments 14, 10, 07 and 04 with 548.09, 481.16, 325.19 and 269 34 nuevos soles. In cost / benefit ratio from 1.38 to 1.12 - 1,07- 1,06. This finding means that the weeding must be done less frequently in due time, between 20-30 days after transplantation in order not to affect the formation of tillers Ios and ensure obtaining the highest number of spikes. 09 treatment (control with weeds throughout the crop cycle) with 10.18 tillers, overcame 16 (weeding Ios 70 days) to reach 9.26 tillers; This observed effect is due to the weed species that existed between them, specifying 16 there was greater number of Cyperaceae, weeds have interaction effect, corroborating the statement Helfgott and Pozo (1986) when they mention that interaction refers competition and allelopathy.